Tibial tubercle avulsion fracture during sport activities in adolescent: a case report - Pedrazzini, Alessio; Maserati, Ilaria; Cesaro, Giuseppe; Visigalli, Alberto; Casalini, Daniele; Bertoni, Nicola; Yewo, Simon Henry; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of work: Tibial tubercle avulsion fractures (TTAF) are uncommon condition in children and adolescents. These lesions may be misdiagnosed and consequently not properly treated. Reduction and fixation is indicated if displacement is higher than 2mm or if the extensor apparatus is damaged. Authors present a case of a TTAF associated with a complete lateral patellar retinaculum lesion in a 13-year-old male adolescent non-professional basketball player. Methods: Surgery consisted of reduction and fixation with 2 half threaded cancellous and washers; TTA was then basted and reinforced with a non absorbable suture according to Krachow technique and finally the patellar lateral retinaculum through a direct repair with absorbable material. Results: Clinical evaluation after 3 years showed bone healing, a complete resolution of pain, complete range of motion, good strength and complete functionality of the operated limb. Conclusions: Misdiagnosis or delayed treatment of TTAF can often result in nonunion, functional impairment, and persistent pain. For these reasons, authors believe that a stable and quick fixation associated to specialized rehabilitation are crucial for recovery. (www.actabiomedica.it)